The effect of angiotensin II receptor blockers on hyperuricemia. (November 2015) - Wolff, Marissa L.; Cruz, Jennifer L.; Vanderman, Adam J.; Brown, Jamie N.
The objective of this review was to explore the efficacy of angiotensin II receptor blockers (ARBs) for the treatment of hyperuricemia in individuals diagnosed with gout or hyperuricemia defined as ⩾7 mg/dl at baseline. A literature search of MEDLINE (1946 to June 2015) and EMBASE (1947 to June 2015) was conducted. The following search terms were used: 'uric acid', 'urate transporter', 'gout', 'angiotensin II receptor blockers', 'hyperuricemia' and the names for individual ARBs, as well as any combinations of these terms. Studies were excluded that did not explore fractional excretion or serum uric acid as an endpoint, if patients did not have a diagnosis of gout or hyperuricemia at baseline, or if they were non-English language. A total of eight studies met the inclusion criteria. Of the eight studies identified, six explored ARB monotherapy and two studies investigated ARBs as adjunct therapy. Losartan demonstrated statistically significant reductions in serum uric acid levels or increases in fractional excretion of uric acid in all studies, whereas no other ARB reached statistical benefit. The effect of ARBs on the occurrence of gout attacks or other clinical outcomes were not represented. Four studies evaluated safety effects of these agents indicating abnormalities such as minor changes in lab values. In conclusion, losartan is the only ARB that has consistently demonstrated a significant reduction in serum uric acid levels, although the significance of impacting clinical outcomes remains unknown. Losartan appears to be a safe and efficacious agent to lower serum uric acid levels in patients with hyperuricemia.